Three-dimensional alterations in pharyngeal airway and maxillary sinus volumes in Class III maxillary deficiency subjects undergoing orthopedic facemask treatment - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2014)
Objective: To assess short-term alterations in the volume of pharyngeal airway space and maxillary sinuses associated with rapid maxillary expansion (RME) and facemask (FM) use in growing Class ill maxillary-deficient patients. Materials and Methods: Twenty-two patients (14 girls, eight boys) treated with the RME/FM and having pretreatment and posttreatment cone beam computed tomographic scans were identified from the archives of the Marmara University, Department of Orthodontics. According to the protraction force that was used, they were divided into two groups: a group with 400 g protraction force (12 subjects) and a group with 800 g protraction force (10 subjects). Mean age for the study group was 10 years. All patients were diagnosed with normal/low vertical growth pattern, maxillary deficiency, and normal mandible. No control group was available for this study. For each patient, a hyrax expansion screw with acrylic cap splint was constructed and RME was performed for 10 days. On the seventh day, protraction with a FM started. Results: The results showed a statistically significant increase in the volume of maxillary sinuses after treatment, which was related to the growth. On the other hand, the increase in the volume of pharyngeal airway was not statistically significant. Conclusions: RME/FM treatment did not affect at all the volume of maxillary sinuses and actually inhibited the normal expected increase of the volume of the pharynx when compared with a control group comprising normal individuals.
Keywords: 3D; Pharyngeal airway space; Maxillary sinuses; Facemask; Rapid palatal expansion; COMPUTED-TOMOGRAPHY; PROTRACTION; DIMENSIONS; EXPANSION; MALOCCLUSION; THERAPY